2017
DOI: 10.1021/acs.langmuir.6b04454
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Reflection Imaging for the Morphology and Dynamics of Live Aplysia californica Pedal Ganglion Neurons Cultured on Nanostructured Plasmonic Crystals

Abstract: We describe a reflection imaging system which consists of a plasmonic crystal, a common laboratory microscope, and bandpass filters for use in the quantitative imaging and in-situ monitoring of live cells and their substrate interactions. Surface plasmon resonance (SPR) provides a highly sensitive method to monitor changes in physicochemical properties occurring at metal-dielectric interfaces. Polyelectrolyte thin films deposited using the layer-by-layer (LBL) self-assembly method provide a reference system to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…1G). The neuronal model used in the present study is Aplysia californica , previously used by Kandel et al to understand the synapse-specific long-term facilitation 30, 31 ; studied pedal ganglion neurons are cholinergic 32, 33, 34 and they were cultured following the well-established protocols 35, 36 , with details shown in the Supporting Information. We employed nanoresolved scanning electrochemical microscopy (SECM) 37, 38, 39, 40, 41, 42 (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1G). The neuronal model used in the present study is Aplysia californica , previously used by Kandel et al to understand the synapse-specific long-term facilitation 30, 31 ; studied pedal ganglion neurons are cholinergic 32, 33, 34 and they were cultured following the well-established protocols 35, 36 , with details shown in the Supporting Information. We employed nanoresolved scanning electrochemical microscopy (SECM) 37, 38, 39, 40, 41, 42 (Fig.…”
mentioning
confidence: 99%
“…The neuronal model used in the present study is Aplysia californica, previously used by Kandel et al. to understand the synapse-specific long-term facilitation; , studied pedal ganglion neurons are cholinergic and they were cultured following the well-established protocols, , with details shown in the Supporting Information. We employed nanoresolved scanning electrochemical microscopy (SECM) (Figure E) to position the nanoelectrode near the synaptic cleft, formed between the axon of one neuron (pink) and the neurite of another neuron (blue) (Figure B,F).…”
mentioning
confidence: 99%
“…The neuronal model in the current study is Aplysia californica , which has been demonstrated as an important model to understand cellular communication and fundamental mechanisms of learning and memory. 26 31 Aplysia contains a large number of neurons of varying sizes, facilitating its isolation and experimentation at the single cell level. 29 , 31 , 32 The release of ACh from the living pedal ganglion neurons of this organism in response to chemical stimulation has not been extensively studied; however, the presence of choline acetyltransferase, the enzyme responsible for the synthesis of acetylcholine, has been observed, 33 , 34 indicating cholinergic activity within these neurons.…”
mentioning
confidence: 99%
“… 26 31 Aplysia contains a large number of neurons of varying sizes, facilitating its isolation and experimentation at the single cell level. 29 , 31 , 32 The release of ACh from the living pedal ganglion neurons of this organism in response to chemical stimulation has not been extensively studied; however, the presence of choline acetyltransferase, the enzyme responsible for the synthesis of acetylcholine, has been observed, 33 , 34 indicating cholinergic activity within these neurons. 34 36 The study of cholinergic release from Aplysia californica neurons contributes to a greater understanding of the role that acetylcholine plays in cellular communication.…”
mentioning
confidence: 99%
“…This is because ASW is the biological cellular medium for an important neuronal model, Aplysia California, which has been successfully used to provide fundamental understanding of brain functions. [20][21][22][23][24][25][26][27][28] Developing the delivery system in ASW well positions us to carry out future z E-mail: mshen233@illinois.edu drug delivery experiments with the presence of the living neurons in the biological medium.…”
mentioning
confidence: 99%